2016
DOI: 10.1111/cmi.12641
|View full text |Cite
|
Sign up to set email alerts
|

Long-term live-cell imaging reveals new roles forSalmonellaeffector proteins SseG and SteA

Abstract: Summary Salmonella Typhimurium is an intracellular bacterial pathogen that infects both epithelial cells and macrophages. Salmonella effector proteins, which are translocated into the host cell and manipulate host cell components, control the ability to replicate and/or survive in host cells. Due to the complexity and heterogeneity of Salmonella infections, there is growing recognition of the need for single cell and live-cell imaging approaches to identify and characterize the diversity of cellular phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 69 publications
3
39
0
Order By: Relevance
“…5A). We extracted all these elements using Icy, an image analysis software program (18) recently used for Salmonella infection studies in situ (19) (Fig. S5A gives an illustration of Icy cell segmentation).…”
Section: Resultsmentioning
confidence: 99%
“…5A). We extracted all these elements using Icy, an image analysis software program (18) recently used for Salmonella infection studies in situ (19) (Fig. S5A gives an illustration of Icy cell segmentation).…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that SteA and PipB2 accumulated on the SCV and membrane tubules in both HeLa and RAW cells 14 . However, primary BMDMs often lack a compact SCV, and instead internalized bacteria are more commonly enclosed within a membrane-bound compartment but spread throughout the cell 7 (Fig. S7), as was observed in infection of human monocyte-derived macrophages 41 .…”
Section: Resultsmentioning
confidence: 83%
“…The importance of live cell imaging for defining the interface between pathogen and host derives from the observation that isolated snap shots often fail to capture complex dynamic phenotypes such as dispersion and coalescence of the SCV 7 , and that cell fixation can alter infection phenotypes, such as the integrity of membrane tubules that emanate from the SCV 1,8 . The need for single cell resolution was motivated by widely observed heterogeneity in infection phenotypes from cell to cell.…”
mentioning
confidence: 99%
See 2 more Smart Citations